Athlete and coach development in the Sevilla Club de Fútbol Youth Academy: A values-based proposition - Solana-Sánchez, A.; Lara-Bercial, S.; Solana-Sánchez, D. (International Sport Coaching Journal, 2016)
Professional youth football (soccer) academies face a number of challenges related to the contrasting and at times competing nature of their goals. Marrying long-term development of players with success in youth competitions and combining the development of young people as athletes with their growth as human beings are some examples. Professional football clubs and those tasked with leading their academies have to make key decisions as to how these challenges will be addressed. In this paper we argue that those decisions must be made based on a clearly shared philosophy and accompanying set of values. We present some of the key principles governing the work of the Sevilla Club de Fútbol Youth Academy and the rationale behind them. These principles span from developmental, methodological and pedagogical choices to the building of an internal long-term approach to coach development.